Association of helicobacter pylori infection with lipid metabolism and 10-year cardiovascular risk in diabetes mellitus: A cross-sectional study - Yuexi Li; Xiaoqin Liu; Qing Li; Peng Zhou; Qian Chen; Bolan Jiang; Taiju Zhu (PLoS ONE, 2025)
Background Previous studies have shown that Helicobacter pylori infection is not only a risk factor for gastrointestinal diseases but also associated with various non-digestive conditions. This study aimed to investigate the effect of Helicobacter pylori infection on the risk of lipid metabolism disorders and cardiovascular disease in individuals with diabetes mellitus. Methods This cross-sectional study was conducted at a health examination center. Data from life questionnaires, laboratory tests, the carbon-13 urea breath test, and the Framingham Risk Score were collected from 266 patients with diabetes. All participants were categorized into Helicobacter pylori-uninfected and Helicobacter pylori-infected groups based on the carbon-13 urea breath test results. Differences in lipid levels, Framingham Risk Score, and cardiovascular disease risk were compared between the two groups. A logistic regression model was applied to analyze whether Helicobacter pylori infection is an independent risk factor for dyslipidemia in patients with diabetes. Results Total cholesterol and low-density lipoprotein cholesterol levels were higher in the Helicobacter pylori-infected group than in the uninfected group, and high-density lipoprotein cholesterol levels were lower in the infected group (both P <  0.05). There was no statistically significant difference in triglyceride levels between the two groups. Regression analysis showed that Helicobacter pylori infection was an independent risk factor for dyslipidemia in patients with diabetes (P <  0.05). The Framingham Risk Score and 10-year cardiovascular disease risk were higher in the Helicobacter pylori-infected group compared with the uninfected group (P <  0.001). Conclusion Helicobacter pylori infection is associated with dyslipidemia and may contribute to an increased risk of cardiovascular disease in individuals with diabetes.